2021
DOI: 10.1111/iwj.13572
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of injection‐related wounds and skin infections amongst persons who inject drugs and use a syringe service programme: A single center study

Abstract: Risk factors associated with wounds and skin infections amongst persons who inject drugs may have changed in the era of fentanyl and now stimulant coinjection. We assessed the number of injection site wounds and skin infections and associated factors amongst 675 persons who inject drugs in a syringe services programme. Of this sample, 173 participants reported a total of 307 wounds and skin infections. Significant factors associated with increased number of wounds and skin infections were age 30 or older, fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Comparable studies have found similarly high prevalence estimates [ 5 , 6 , 8 ]. Previous studies have also found injection of specific types of stimulants to be associated with increased SSTI occurrence [ 5 , 31 35 ]. In line with this, we found cocaine and crack-cocaine injection were associated with an increased prevalence of recent SSTI history.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable studies have found similarly high prevalence estimates [ 5 , 6 , 8 ]. Previous studies have also found injection of specific types of stimulants to be associated with increased SSTI occurrence [ 5 , 31 35 ]. In line with this, we found cocaine and crack-cocaine injection were associated with an increased prevalence of recent SSTI history.…”
Section: Discussionmentioning
confidence: 99%
“…In another study from the United Kingdom (UK), factors associated with bacterial SSTI were older age (older than 35 years), reusing needles and four or more attempts to achieve an injection [8]. Furthermore, homelessness is frequently observed in patients with IDU-associated SSTIs and is likely related to barriers to proper skin cleaning prior to injections [15 ▪▪ ,25]. These results reflect the importance of sociodemographic aspects when evaluating high-risk injection practices.…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 98%
“…PWID are faced with many health risks, including increased risk of premature mortality, HIV, hepatitis C virus (HCV), hepatitis B virus (HBV), injection-related wounds, 10 and SSTIs. 2 , 11 Wounds and SSTIs are common complications of IDU and disproportionately affect PWID.…”
Section: Clinical Relevancementioning
confidence: 99%
“… 2 , 11 Wounds and SSTIs are common complications of IDU and disproportionately affect PWID. 4 , 10 , 12 Wounds and SSTIs in PWID may contribute further to addiction as patients seek to reduce the pain and may lead to worse outcomes ( e.g., sepsis, gangrene, amputation). 5 , 12 The synergistic provision of wound care at syringe services program (SSP) is proposed as a unique upstream access solution for this high priority population.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation